(untitled) (Terr@ Plural, 2020)
Geodiversity of value must be conserved and thus bring benefits to the local population. The goal of this study was to analyze the perception of João Dourado inhabitants regarding their geodiversity, as well as to seek suggestions from the residents on its geoconservation. The opinion survey was carried out with 280 residents and we found that 254 respondents understand that the city’s rocks, water, and caves are considered as heritage and 231 believe that they may have associated economic value. Most people show confidence in the benefits that geodiversity could offer in economic and social terms, such as attracting geotourists to the city.